Nomadconnect / Adam Francis ... [et al.] - Francis, Adam; Blwon, Franz; Vui Hua, Lam; Bohari, Mohd Faizal; Hazmi, Helmy (2024)
NomadConnect is a new product that aims to make it easier to record clinical data about patients in places where internet access is hard. UNIMAS Teaching Hospital and Medical Centre (HPPPU) has been entrusted with implementing health programmes for the underserved population of Sarawak. Capturing and retrieving patients' clinical data is a problem during a mission as multiple service providers attempt to access relevant information about the clients, ranging from registration to clinical assessment and drug prescription. Methods tried so far include the use of manual forms leading to difficult paper management, the use of ReKa cloud services limited by scarce internet access in rural areas, and Excel VB limitations in combining databases and post-mission data cleaning for analysis. Therefore, NomadConnect, a mobile patient data management system, attempts to resolve these issues by functioning without an internet connection. It does this by using a portable server system and giving users easy access to the integrated databases. The result is that patient data can be collected quickly, making it easier for patients to move through the stations and giving clinicians and providers more time to focus on better patient care rather than a broken system and quick data analysis that needs to be shared with the relevant people. In summary, NomadConnect is an important toolkit for on-site patient management with poor internet access for those who want to provide health services in rural areas.